Differential effects of indirubin and 2,3,7,8-tetrachlorodibenzo-p-dioxin on the aryl hydrocarbon receptor (AhR) signalling in liver progenitor cells - Procházková, Jiřina; Kozubík, Alois; Machala, Miroslav; Vondráček, Jan (Toxicology, 2011)
In the present study, we investigated the effects of potential endogenous ligand indirubin on the aryl hydrocarbon receptor (AhR) signalling, with a focus on the AhR-dependent gene expression and cell cycle progression in rat liver progenitor cells, and compared them with the effects of a model toxic AhR ligand, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). The low (picomolar and nanomolar) doses of indirubin, corresponding to expected endogenous levels, induced a transient translocation of AhR to the nucleus, while high (micromolar) doses induced a long-term AhR nuclear translocation, followed by its degradation, similar to the effects of TCDD. Whereas high doses of indirubin recruited AhR/ARNT1 dimer to rat Cyp1a1 promoter, the low doses did not induce its DNA binding, as revealed by the chromatin immunoprecipitation assay. This corresponded with the fact that the micromolar doses of indirubin significantly increased Cyp1a1/1b1 mRNA in a way similar to TCDD, while the low doses of indirubin were only poor inducers of Cyp1a1/1b1 expression. Comparable patterns of expression were observed also for other AhR gene targets, such as Nqo1 and Nrf2. Also, only micromolar doses of indirubin were able to mimic the effects of TCDD on cell cycle and proliferation of liver progenitor cells or hepatoma cells. Nevertheless, indirubin at low concentrations may have unique effects on gene expression in non-tumorigenic cells. Although both TCDD and the high doses of indirubin repressed plakoglobin (Jup) expression, the picomolar doses of indirubin, unlike the equimolar doses of TCDD, increased mRNA levels of this important desmosomal and adherens junctions constituent. These present data suggest that the outcome of AhR activation induced by indirubin at concentrations expected in vivo may differ from the AhR signalling triggered by exogenous toxic ligands, such as TCDD.
Keywords: Gene Expression Regulation; receptory aromatických uhlovodíků; Cell Nucleus; Cell Proliferation; indoly; signální transdukce; Carcinoma, Hepatocellular; vztah mezi dávkou a účinkem léčiva; buněčné jádro; transport proteinů; Polychlorinated Dibenzodioxins; Signal Transduction; krysa rodu Rattus; Stem Cells; kultivované buňky; Animals; játra; Indoles; zvířata; regulace genové exprese; Rats; Cell Cycle; hepatocelulární karcinom; chromatinová imunoprecipitace; proliferace buněk; polychlorované dibenzodioxiny; Protein Transport; Cells, Cultured; buněčný cyklus; Liver; Liver Neoplasms; Dose-Response Relationship, Drug; nádory jater; kmenové buňky; Receptors, Aryl Hydrocarbon; Chromatin Immunoprecipitation